Implementation of Collaborative Policy for Tourism Village Development in Bintan Regency, Riau Islands Province - Ambiya, Mohd. Zamir (Syntax Corporation Indonesia, 2024)
This study was conducted to determine the Implementation of Collaborative Policy for Tourism Village Development in Bintan Regency, Riau Islands Province. Tourism has experienced a very rapid development so that the demand for varied tourist objects and destinations is getting higher, the presence of tourist villages is one of the answers to these needs. The role of the government and related stakeholders is becoming increasingly important in collaborating to respond to these developments. This research is designed descriptively - qualitatively. To see the Policy Implementation of Bintan Regent Regulation No. 31 of 2022 concerning tourist villages and villages, researchers used Ryan Nugroho's Policy Implementation Theory (2004: 159) and Emerson, Nabatchi and Ballough's Collaboration Theory (2012). This research was conducted in the tourist village of Bintan Regency, Riau Islands Province. The results showed that the implementation of the collaborative tourism village development policy in Bintan Regency has not been effective. This is due to the low proactivity of collaboration elements. To address this challenge, the research designed a collaboration model called the